الجامعات الإسلامية في أمريكا وأوروبا رسالة العلم والسّلام - بلهامل، مفيدة (University Of Eloued جامعة الوادي, 2024)
تواجه محاولة دراسة الجامعات الإسلامية في أمريكا وأوروبا الاختلاف الواضح بين الكتابات الغربية والعربية في التأريخ للتعليم العالي وكذا لأولى الجامعات في أوروبا وهذا بطبيعة الحال قبل ظهور أمريكا وتوجه الكتابات الغربية في حصر ربط التأسيس لهذا الموضوع -التعليم الجامعي العالي -في أوروبا والتجاهل التام لدور المسلمين في ذلك خاصة وأن الازدهار العلمي الوحيد الذي عرفته أوروبا و حصريا وقبل ظهور حتى عدد كبير من الدول الأوروبية نفسها ارتبط بالأندلس فقط وبقرطبة تحديدا التي ظهرت في وقتها من حيث التألق والمستوى العلمي والحضاري عاصمة الخلافة الإسلامية نفسها في المشرق الإسلامي ولم يكن حينها غير هذا في العالم أجمع وكم كان طموح النخبة الإسلامية منذ نشأة رابطة العالم الإسلامي في 1962-وبعدها منظمة المؤتمر الإسلامي - في 1969في أن تمد عنايتها إلى الاهتمام بمراكز وجامعات التعليم الإسلامية عبر العالم ومنها في أوروبا وأمريكا وهو ما كان يدخل في صميم أهدافها وعلى أعلى مستوى رسمي حينها، ، ، في محاولة منها لربط المسلمين -شعوبا وجاليات - فيما يحقق توجه عنوانها الكبير وخاصة بعدما استقلت معظم الدول الإسلامية في نهاية الستينات من القرن المنصرم، وذلك عبر مؤسساتهم التعليمية والعالية منها - المعاهد والجامعات -بالاطلاع على ظروفها ومشكلاتها وواقع الدراسة فيها ومناهجها، وبهدف تعميم الإفادة والاستفادة عموما وفعلا انبثق من تلك المجهودات الطيبة الجادة والطموحة إيفاد -رابطة العالم الإسلامي -العلماء للاشتغال بهذا الموضوع عبر أوروبا و أمريكا وكانت باكورة ذلك الكتب و التقارير عن 28 دولة في أوروبا و13دولة في أمريكا واستمرت في الاهتمام بهذا الانشغال وغيره في كتب دورية تهتم وتجمع وتتابع وتواكب وتنشر، لتؤسس بوادر الاهتمام بهذا الموضوع الذي اختاره للبحث والدراسة ستعرض المداخلة لهذه المجهودات وستحاول أن تربط بينها وبين جديد الجامعات الإسلامية عبر ما تيسر من مراجع ومقالات بالاطلاع والجمع والتصنيف والتعريف ما أمكن لتقدم كشافا بالموضوع وتريده مجهودا استمراريا لما سبق وتأسيسيا لمستقبل هذا الانشغال العلمي الهام Abstract: The attempt to study Islamic universities in America and Europe faces the clear difference between Western and Arab writings in the history of higher education as well as the first universities in Europe. This, of course, was before the emergence of America. Western writings tended to limit the establishment of this topic - higher university education - to Europe and completely ignore the role of Muslims in This is especially so since the only scientific prosperity that Europe knew exclusively, and before the emergence of even a large number of European countries themselves, was linked to Andalusia only and to Cordoba in particular, which appeared at its time in terms of brilliance and scientific and civilizational level as the capital of the Islamic Caliphate itself in the Islamic East, and at that time there was nothing else in the entire world. How ambitious has been the Islamic elite since the inception of the Organization of the Islamic Conference in 1969 to extend its attention to Islamic education centers and universities across the world, including in Europe and America, which was at the core of its goals and at the highest official level at the time, in an attempt to connect Muslims as peoples. And communities - while achieving the direction of its great title, especially after most Islamic countries gained independence at the end of the sixties of the last century, through their educational institutions, including higher education - universities - by learning about their conditions and problems and the reality of studying there and its curricula, and with the aim of spreading benefit and benefit in general. Indeed, out of those good, serious and ambitious efforts emerged the dispatch of - the Muslim World League - scholars to work on this subject across Europe and America. The first of these were books and reports on 28 countries in Europe and 13 countries in America, and this and other enthusiasms continued in periodic books that concerned, collected, followed up, kept up with and published, to establish signs of interest. With this topic he chose for research and study The intervention will present these efforts and will attempt to link them to new Islamic universities through the available references and articles by reviewing, collecting, classifying and defining them as much as possible to provide an overview of the subject and want it to be a continuation effort of what came before and a foundation for the future of this important scientific concern.
دراسة استطلاعية تعريفية
مداخلة
Keywords: الجامعات الإسلامية; أمريكا; أوروبا; العلم والسّلام; دراسة استطلاعية تعريفية